Neurosteroids as Selective Inhibitors of Glycine Receptor Activity: Structure-Activity Relationship Study on Endogenous Androstanes and Androstenes - Bukanova, Julia V.; Solntseva, Elena I.; Kudova, Eva (Frontiers in Molecular Neuroscience, 2020)
The ability of androstane and androstene neurosteroids with modifications at C-17, C-5, and C-3 (compounds 1-9) to influence the functional activity of inhibitory glycine and γ-aminobutyric acid (GABA) receptors was estimated. The glycine- and GABA-induced chloride current (IGly and IGly) were measured in isolated pyramidal neurons of the rat hippocampus and isolated rat cerebellar Purkinje cells, correspondingly, using the patch-clamp technique. Our results demonstrate that all the nine neurosteroids display similar biological activity, namely, they strongly inhibited IGly and weakly inhibited IGABA. The threshold concentration of neurosteroids inducing effects on IGly was 0.1 μM, and for effects on IGABA was 10-50 μM. Moreover, our compounds accelerated desensitization of the IGly with the IC50 values varying from 0.12 to 0.49 µM and decreased the peak amplitude with IC50 values varying from 16 to 22 µM. Interestingly, our study revealed that only compounds 4 (3β-hydroxy-5α-androstan-17-one) and 8 (dehydroepiandrosterone) were able to cause a significant change in IGABA in 10 µM concentration. Moreover, compounds 3 (testosterone), 5 (epitestosterone), 6 (5α-androstandione), and 9 (5β-androstendione) did not modulate IGABA up to the concentration of 50 μM. Thus, we conclude that compounds 3, 5, 6, and 9 may be identified as selective modulators of IGly. Our results offer new avenues of investigation in the field of drug-like selective modulators of IGly.